Ultrasonic Extraction-Gas Chromatography-Mass Spectrometry for Determination of Eight Organophosphorus Flame Retardants in Coatings - ZHANG Ying; LI Yi; CHEN Yezi; WANG Xutao (Renmin Zhujiang)
A method for the simultaneous determination of eight organophosphorus flame retardants (OPFRs) in coatings is developed with ultrasonic extraction for preprocessing and gas chromatography-mass spectrometry (GC-MS).The comparison and optimization of experimental conditions in the ultrasonic extraction process indicate that acetone should be taken as the extraction solvent,and the extraction temperature and time should be set to 30 ℃ and 15 min,respectively;when the extraction is repeated twice,the recovery is good.Quantitative analysis is performed by GC-MS with selective ion scanning,with the linear range of the standard preparation curves being 10~1 000 ng/mL.The results demonstrate that the correlation coefficients of linear regression equations for eight OPFRs are not less than 0.990 4.The detection limits of the method are between 0.04 and 0.26 ng/mL,with the recovery of 79.3%~112.0%,and the relative standard deviations are less than or equal to 6.4%.The application of the method to the determination of OPFRs in coating products from five enterprises shows that TCEP is detected in samples of only one enterprise,with a concentration of 15.22 ng/mL.